Size-dependent nonlinear thermomechanical in-plane stability of shallow arches at micro/nano-scale including nonlocal and couple stress tensors - Yang, Zhicheng; Barbaros, Ismail; Sahmani, Saeid; Nuhu, Abubakar Abdussalam; Safaei, Babak (Taylor & Francis Inc, 2024)
In the present exploration, the unconventional tensors of nonlocal stress and couple stress are incorporated simultaneously in the in-plane nonlinear stability analysis of functionally graded (FG) multilayer shallow micro/nano-arches under thermomechanical loading conditions. For this purpose, the nonlocal couple stress (NCS) mechanics of continuum is implemented into the third-order shear flexible arch theory incorporating the von Karman kinematical nonlinearity. The nanocomposite material of FG multilayer shallow micro/nano-arches is reinforced with graphene nanofillers in accordance with different patterns of FG lamination. The generalized differential quadrature numerical strategy in conjunction with the pseudo arc-length continuation procedure are employed to deduce the roles of unconventional nonlocal and couple stress tensors in the NCS-based nonlinear stability paths of thermomechanical loaded FG multilayer shallow micro/nano-arches. It is found that for all patterns of the lamination, the contributions associated with the nonlocality and couple stress small scale effects on the value of the upper limit as well as the first bifurcation compressive loads are less than those on the lower limit and the second bifurcation ones. Also, it is demonstrated that by combining a temperature rise with the applied compressive lateral load, the upper limit lateral load increases, while the lower limit one decreases. Furthermore, it is seen that by applying a temperature rise, an initial lateral deflection is induced in the shallow micro/nano-arch before applying the compressive lateral load.
Keywords: Micromechanics; numerical solution strategy; shallow arches; unconventional continuum elasticity; nanocomposite materials